Kierkegaard and Spirituality : Accountability As the Meaning of Human Existence. - Evans, C. Stephen (Kierkegaard As a Christian Thinker Ser., 2019)
"Evans reminds us that while Kierkegaard is a distinct Christian thinker, anyone interested in spirituality broadly understood has something to gain from one of the great masters of the human spirit. This book successfully demonstrates that Kierkegaard's psychology and theology cannot be separated and that if you are interested in one, you must confront the other."